Political, military and cultural impact of the North African muslims on the United States during the first years of the early republic : 1783-1807 - Palotás, Zsolt (Études sur la Région Méditerranéenne, 2015)
The North African Barbary States (Morocco, Algiers, Tunis and Tripoli) and the United States of America maintained various relations in the Early Modern Times. After the War of Independence the relations became rather problematic between the two cultures. In the American mind, relations with the Barbary States have been generally associated with issues of commerce, piracy, captivity, tribute and war. The American merchants and sailors were captured several times by muslim corsairs after the Revolutionary War. The confederation, however, was powerless in foreign matters and there was a need to centralize the government. At the same time, in the early 1800s several sea narratives and captivity narratives were published about the Americans. This had an important impact on American literature. Furthermore, the first foreign war of the United States was against Tripoli between 1801-1805. Historians connect this war with the birth of the US Navy and Marine Corps. After the Tripolitan War, the Americans citizens met an illustrious muslim diplomata as well. Sidi Soliman Mellimelli, the Tunisian envoy was the first Muslim ambassador in the USA between 1805 and 1806.